2022
DOI: 10.1111/bjop.12586
|View full text |Cite
|
Sign up to set email alerts
|

Alternating time spent on social interactions and solitude in healthy older adults

Abstract: Time spent on being with others (social interactions) and being alone (solitude) in day to day life might reflect older adults' agentic regulatory strategies to balance the needs to belong and to conserve energy. Motivated from a joint lifespan psychological and social relationship theoretical perspective, this study examined how time spent on social interactions and solitude alternatively unfolds within individuals in daily life, relating to individual differences in trait-level well-being and fatigue. Over 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 102 publications
1
10
0
Order By: Relevance
“…For example, it is known that older adults are selective in maintaining emotionally close social relations and social engagement, often reducing and focusing social contacts on a select number (Lang et al, 2002; Wrzus & Neyer, 2016). In addition, daily activity engagement is governed by motivation to engage as well as motivation to conserve energy (Cardini & Freund, 2020; Luo, Pauly, et al, 2022). In line with the notion of functional capacity as resulting from personal resources and individual environmental affordances, activity engagement patterns likely result in a wide range of how diversity may best be implemented across different individuals and across different life span periods, so as to represent what is most meaningful to each individual (World Health Organization, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is known that older adults are selective in maintaining emotionally close social relations and social engagement, often reducing and focusing social contacts on a select number (Lang et al, 2002; Wrzus & Neyer, 2016). In addition, daily activity engagement is governed by motivation to engage as well as motivation to conserve energy (Cardini & Freund, 2020; Luo, Pauly, et al, 2022). In line with the notion of functional capacity as resulting from personal resources and individual environmental affordances, activity engagement patterns likely result in a wide range of how diversity may best be implemented across different individuals and across different life span periods, so as to represent what is most meaningful to each individual (World Health Organization, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The study design, the hypotheses, and the analytic plan for this study were preregistered (Luo et al, 2021a). The materials, the de-identified data, the analyses code, and the detailed results (Luo et al, 2021b) are available at the links in the Author Note section. All multilevel models were estimated in R (R Core Team, 2013) using the R package lme4 Version 1.1-27.1 (Bates et al, 2007) and lmerTest Version 3.1-3 (Kuznetsova et al, 2017).…”
Section: Methods Transparency and Opennessmentioning
confidence: 99%
“…For example, research has shown that the effects of social activities on health and well-being are subjected to the law of diminishing returns, such that the beneficial effects have upper limits within a certain timeframe (Ren et al, 2022; Stavrova & Ren, 2021). This provides hints that once the effects of an activity wane, individuals might need to return to further activity engagement (Luo, Pauly, et al, 2022). Thus, it is necessary to devote research to understand how long an effect of one bout of activity engagement on cognitive performance may last.…”
Section: “How To” Engage In Everyday Activities To Benefit Cognitive ...mentioning
confidence: 99%
“…Older adults also need more time for recovery and self-care (Lang & Baltes, 1997). This, in combination with the fact that social interactions require more energy than earlier in life, might increase the need for solitary time to replenish (Luo et al, 2022). Finally, social role losses (e.g., retirement) and the death of loved ones limit social interaction opportunities and increase solitude (Baltes & Smith, 2003).…”
Section: Normative Age-graded Influences On Solitudementioning
confidence: 99%
“…However, solitude can also be experienced positively (Lay et al, 2019). For example, solitude can foster recovery, creativity, and self-reflection (Long & Averill, 2003; Luo et al, 2022). Having too little solitude can have negative well-being ramifications as well (Coplan, Hipson et al, 2019; Prime et al, 2020).…”
Section: Introductionmentioning
confidence: 99%